2010
DOI: 10.1007/s15010-009-9253-1
|View full text |Cite
|
Sign up to set email alerts
|

Hospital-Acquired Pneumonia and Bacteremia Caused by Legionella pneumophila in an Immunocompromised Patient

Abstract: The Legionella species is an important cause of communityand hospital-acquired pneumonia. Bacteremic pneumonia caused by L. pneumophila is rarely reported. We describe the first reported case of hospital-acquired pneumonia and bacteremia caused by L. pneumophila from Taiwan in a patient with idiopathic thrombocytopenic purpura who received steroid treatment. The patient was successfully treated with ceftazidime and clindamycin initially, followed by ciprofloxacin for 14 days. The blood isolate was further conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…pneumophila was actually very few [30][31][32], this case suggests that blood culture is worth trying when UAT results are negative and sputum is not discharged when LD is suspected.…”
Section: Discussionmentioning
confidence: 99%
“…pneumophila was actually very few [30][31][32], this case suggests that blood culture is worth trying when UAT results are negative and sputum is not discharged when LD is suspected.…”
Section: Discussionmentioning
confidence: 99%
“…1 Since March 2014, more than 27,000 cases of Ebola virus disease and 11,000 deaths have been reported in West Africa. 2 Healthcare workers are between 21 and 32 times more likely to be infected with Ebola virus than people in the general population. 3 In light of this current outbreak and its high case-fatality rate, a broad range of challenges were reported, including conflicting PPE removal protocols and gaps in training and supplies.…”
Section: Infectious Diseases Of High Consequence and Personal Protectmentioning
confidence: 99%
“…Nadim Cassir, MD; 1,2 Sophia Boudjema, NP; 1,2 Valérie Roux, NP; 2 Pauline Reynier; 1 Philippe Brouqui, PhD The Pearson χ 2 test was used to perform 2-group comparisons for qualitative variables; the Fisher exact test was used when the expected count was <5. A multivariate analysis using logistic regression was performed to identify independent risk factors for contamination.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…25,26 In South Africa, the first investigation of an outbreak of LD in a Johannesburg teaching hospital in 1985 reported 12 cases in hospitalised patients, with two patients confirmed to have acquired the disease in the hospital. 27 A more recent surveillance study of two South African hospitals by Wolter et al 28 reported Legionella in 21 (1.2%) cases of patients diagnosed with HIV or tuberculosis infections.…”
Section: Discussionmentioning
confidence: 99%